Reversible endoscopic gastroduodenal bypass for the treatment of persistent duodenal leaks after failed surgical repair: a pilot feasibility study - Kadkhodayan, Kambiz; Chandan, Saurabh; Viana, Artur; Hayat, Maham; Cosgrove, Natalie; Arain, Mustafa A; Jain, Deepanshu; Abassi, Abdullah; Pathak, Sagar; Yang, Dennis; Hasan, Muhammad Khalid; Rosales, Armando; Redan, Jay; Irani, Shayan (Endoscopy, 2025)
Post-surgical leaks following surgical repair of acute duodenal perforations carry high mortality. Reversible endoscopic gastroduodenal bypass (REGB) is a novel procedure that helps divert the acid-rich gastric stream away from the affected duodenum to promote tissue healing at the ulcer site.REGB is a single-session, two-step procedure involving the creation of an endoscopic ultrasound-guided gastrojejunostomy using a lumen-apposing metal stent, followed by endosuturing and closure of the pylorus to achieve complete duodenal bypass. The outcomes of REGB and its reversal were prospectively evaluated in six patients with persistent post-surgical duodenal leaks.REGB was technically successful in all six patients (100%) with no procedure-related adverse events. All patients resumed oral intake within 3 days, experienced significant reductions in surgical drain output, and were discharged. One patient with metastatic breast cancer did not undergo REGB reversal. Among five patients who underwent REGB reversal after a mean of 52.6 days, technical success was achieved in all (100%), with complete healing of duodenal ulcers, absence of leaks on fluoroscopy, and resumption of a solid food diet.REGB is a technically feasible, reversible, and minimally invasive alternative for managing post-surgical duodenal leaks. Further studies are needed to validate its safety and efficacy.